A Single Question of Parent-Reported Physical Activity Levels Estimates Objectively Measured Physical Fitness and Body Composition in Preschool Children: The PREFIT Project - Palou, Pere; Muntaner-Mas, Adrià; Cantallops, Jaume; Borràs, Pere Antoni; Labayen, Idoia; Jiménez-Pavón, David; Dorado García, Cecilia; Moliner-Urdiales, Diego; Rodríguez Pérez, Manuel A.; Rojo-Tirado, Miguel A.; Cadenas-Sanchez, Cristina; Ortega, Francisco B.; et al. (Frontiers in Psychology, 2019)
Physical inactivity is recognized as a determinant of low physical fitness and body composition in preschool children, which in turn, are important markers of health through the lifespan. Objective methods to assess physical activity, physical fitness and body composition in preschool children are preferable; however, they have some practical limitations in the school context. Therefore, the aim of this study was to test whether a single question regarding physical activity level of preschool children, reported by their parents, could be used as an alternative screening tool of physical fitness and body composition. The information was obtained from 10 different cities throughout Spain, gathering a total of 3179 healthy preschool children (52.8% boys and 47.2% girls) aged 3 to 5 years. Physical activity levels of preschool children were reported by parents using a single question with five response options (very low, low, average, high, or very high). Physical fitness and body composition were assessed with the PREFIT fitness battery. The results showed that parents’ perception of their children’s physical activity was positively associated with all objectively measured physical fitness components (βrange= -.094 to .113; all P < .020); and negatively with body composition indicators as measured (βrange= -.113 to -.058; all P < .001). The results showed significant differences in all physical fitness and body composition z-scores across the parent-reported physical activity levels (all p<.017 and all p<.001, respectively), as well as, for the fitness index (p<.001). Our study suggests that in school settings with insufficient resources to objectively assess fitness and body composition, parents-reported physical activity level by means of a single question might provide useful information about these important health markers in preschool children.